Linear Metallopolymers from Ruthenium(II)‐2, 6‐di(quinolin‐8‐yl)pyridine Complexes by Electropolymerization – Formation of Redox‐Stable and Emissive Films. Issue 24 (26th June 2013) - Friebe, Christian; Görls, Helmar; Jäger, Michael; Schubert, Ulrich S.
Abstract: Two rodlike ruthenium(II) complexes of 2, 6‐di(quinolin‐8‐yl)pyridines (dqp) were synthesized and possess a pair of 2‐thienyl moieties attached to the 4‐positions of the quinoline units of one ligand or at the 4‐positions of the pyridine rings of both ligands. The heteroleptic and homoleptic complexes were characterized by UV/Vis absorption and emission spectroscopy as well as electrochemical and X‐ray crystallographic means. The subsequent electropolymerization of the thiophene units led to the controlled formation of thin solid films onto electrode surfaces as proven by X‐ray photoelectron spectroscopy (XPS). The electrochemical analysis of the films was complemented by UV/Vis spectroscopy and UV/Vis/NIR spectroelectrochemistry, which revealed their stability towards oxidation, red emission, and reversible redox switching of their optical properties. Density functional theory (DFT) calculations were executed on the monomer complexes and respective dimeric systems to gain insight into their spectroscopic and electrochemical properties. Abstract : Rodlike polymer assemblies containing thiophene‐equipped ruthenium(II)‐2, 6‐di(quinolin‐8‐yl)pyridine complexes are deposited onto electrode surfaces by applying an electropolymerization approach. The films display the defined and reversible electrochemical switchability of the ruthenium center as well as red luminescence under ambient conditions.